Pengaruh Motivasi Kerja dan Displin Kerja Terhadap Kinerja Karyawan pada PT. Intrias Mandiri Sejati Jakarta Selatan - Arif, Fathan; Tiara, Citra Arip (Lembaga Otonom Lembaga Informasi dan Riset Indonesia (KITA INFO dan RISET) - Lembaga KITA, 2024)
This research aims to analyze the influence of work motivation and work discipline partially or simultaneously on the performance of PT employees. Intrias Mandiri Sejati, South Jakarta. The research method used was quantitative using a sampling technique in the form of saturated sampling, and the number of respondents in this study was 67 people. Data analysis involves validity testing, reliability testing, classical assumption testing, regression analysis, correlation coefficient analysis, coefficient of determination analysis, and hypothesis testing. From the results of the regression analysis, the regression equation Y = 13.391 + 0.528X1 + 0.196X2 is obtained. The correlation coefficient value between the independent variables (work motivation and work discipline) and the dependent variable (employee performance) is 0.698, indicating a strong relationship between these variables. The coefficient of determination value is 48.8%, indicating that employee performance variability can be explained by work motivation and work discipline, while the remainder (51.2%) is influenced by other factors not examined in this research. In hypothesis testing, the calculated F value is 30.459 > F table (2.750), H0 is rejected and H3 is accepted. This means that there is a significant simultaneous influence between work motivation and work discipline on employee performance at PT. True Independent Intrias